2010
DOI: 10.1111/j.1438-8677.2009.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

The polycotyledon (pct1-2) mutant of tomato shows enhanced accumulation of PIN1 auxin transport facilitator protein

Abstract: The bilateral symmetry of a dicotyledon embryo is tightly associated with the directional flow of auxin. Disruption of polar auxin flow results in various developmental abnormalities. The pct1-2 mutant of tomato, showing polycotyledony, also has enhanced polar auxin transport in hypocotyls. Immunocytochemical analysis revealed increased PIN1 protein in pct1-2 roots and hypocotyls. The mutant also displayed an increase in PIN1 transcript levels in these organs. Our results indicate that over-accumulation of PIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The pct1-2 mutant of tomato displays nearly 3-fold faster polar auxin transport that is associated with increased expression of the PIN1 auxin transporter in roots (Al-Hammadi et al, 2003;Kharshiing et al, 2010). Consistent with our hypothesis, time-lapse imaging of root penetration in pct1-2 demonstrated that, in contrast to the wild type, pct1-2 roots had nearly normal penetration in the Soilrite in the presence of 1-MCP, with only occasional seedlings showing an aerial root ( Fig.…”
Section: An Auxin Transport Mutant Displays Normal Root Penetration Imentioning
confidence: 99%
“…The pct1-2 mutant of tomato displays nearly 3-fold faster polar auxin transport that is associated with increased expression of the PIN1 auxin transporter in roots (Al-Hammadi et al, 2003;Kharshiing et al, 2010). Consistent with our hypothesis, time-lapse imaging of root penetration in pct1-2 demonstrated that, in contrast to the wild type, pct1-2 roots had nearly normal penetration in the Soilrite in the presence of 1-MCP, with only occasional seedlings showing an aerial root ( Fig.…”
Section: An Auxin Transport Mutant Displays Normal Root Penetration Imentioning
confidence: 99%
“…The initiation of shoot primordia involves YUCCA regulated auxin biosynthesis and transport facilitated by PIN1 transporter [57]. In conformity with above, IAA levels were higher in RS of pct1-2 mutant that over-accumulates PIN1 protein [27]. The reduction in IAA levels in RS of shr mutant is likely related to the multifaceted interactions of NO with plant hormones [31].…”
Section: Discussionmentioning
confidence: 81%
“…Consistent with this shoot regeneration in Arabidopsis pin1-4 mutant is reduced to 1/5 of wild-type [14]. In view of above role of PIN1 in calli formation, we compared metabolic shifts with the polycotyledon ( pct1-2 ) mutant of tomato that shows enhanced polar auxin transport associated with elevated level of polar auxin transporter PIN1 protein [26], [27]. …”
Section: Introductionmentioning
confidence: 93%
“…Downregulation of the GA biosynthesis gene GA20OX showed delayed flowering in FR enriched environment suggesting a role for this gene in phytochrome-dependent flowering (Hisamatsu and King, 2008). While the association of light and auxin signaling is well established, the tomato pct1-2 mutant having enhanced polar transport of auxin shows delayed phototropism (Kharshiing et al, 2010a,b) as well as increased number of flowers which bloom at the same time as compared to wild type which have lesser flowers and which bloom sequentially (Al-Hammadi et al, 2003). However, the flowers of the pct1-2 mutant are male sterile because the anthers lack dehiscence.…”
Section: Photoreceptors and Phytohormones: Light Mediated Hormonal Rementioning
confidence: 99%